A proxy for all seasons? A synthesis of clumped isotope data from Holocene soil carbonates. (15th April 2020) - Kelson, Julia R.; Huntington, Katharine W.; Breecker, Daniel O.; Burgener, Landon K.; Gallagher, Timothy M.; Hoke, Gregory D.; Petersen, Sierra V.
Abstract: Soil carbonates are important paleoclimate archives, but interpretations of their isotopic compositions (δ 18 O, δ 13 C, and Δ47 ) are hampered by uncertainty in the annual timing of their accumulation. Several previous studies have inferred the annual timing of soil carbonate formation by comparing modern air/soil temperatures with temperatures estimated from the clumped isotopic composition (TΔ47 ) of Holocene soil carbonates. Here, we compile the existing Δ47 data to first consider if recent changes in Δ47 standardization methods alters the apparent seasonal biases. Then we explore the importance of various environmental parameters on soil carbonate TΔ47 and discuss implications for associated paleoclimate reconstructions. Most soil carbonates record TΔ47 values higher than mean annual air temperature, but the residual varies from −4 to +24 °C. Δ47 values for most observed soil profiles do not vary with depth. We find that the grain size of the soil matrix, timing of precipitation, and presence of vegetation each explain a portion of the observed variance in seasonal bias and can be used to aid in interpretations of TΔ47 values from paleosols. In some soil carbonates, a warm-season bias in TΔ47 is accompanied with calculated δ 18 O values of soil water that appear to be biased toward the δ 18 O of summer rainfall. Most estimated values of δ 18 O of soil water are within 2‰ of the δ 18 O values of mean annual rainfall. Where possible, paleoclimate reconstructions should consider precipitation timing, soil texture, and vegetation cover to aid in identifying the seasonal bias of soil carbonate stable isotopic compositions. Highlights: Clumped isotope data from Holocene pedogenic carbonates are recalculated using the 17 O correction parameters of Brand et al. (2010). Most clumped isotope-derived estimates of soil temperature appear to be warm-season biased, but with significant variation. The oxygen isotope composition of soil carbonates can be biased toward the isotopic composition of rainfall from the season in which carbonate forms. Paleoclimate reconstructions should consider that the seasonal bias of this proxy might vary with environmental conditions.